2021
DOI: 10.1186/s42269-021-00660-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of caffeine on delayed-onset muscle soreness: a meta-analysis of RCT

Abstract: Background There are multiple strategies that have been suggested to attenuate delayed-onset muscle soreness (DOMS). Caffeine has been shown to assist with blocking pain associated with DOMS. However, currently there is still controversy over the effects of caffeine use. Main body We conducted a meta-analysis to compare pain associated with muscle soreness by both the VAS and indirect markers by CK of caffeine and placebo after exercise. The meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Accordingly, it has been suggested that pre-exercise caffeine intake could improve perceived muscle damage [ 40 ]. In this regard, a meta-analysis revealed that caffeine decreased muscle damage after 48 h post-exercise compared to a placebo [ 73 ]. Thus, in this study, the participants trained on Tuesdays, Thursdays, and Fridays, with the results coinciding with the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been suggested that pre-exercise caffeine intake could improve perceived muscle damage [ 40 ]. In this regard, a meta-analysis revealed that caffeine decreased muscle damage after 48 h post-exercise compared to a placebo [ 73 ]. Thus, in this study, the participants trained on Tuesdays, Thursdays, and Fridays, with the results coinciding with the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that muscle pain reaches its peak 24 hours after exercise (Ayubi et al 2022;Chang et al 2021;Hung et al 2021;Muljadi et al 2021). In connection with this phenomenon, currently, around 30 million people worldwide who experience DOMS are usually treated with non-steroidal anti-inflammatory drugs (NSAIDs) (Ayubi and Sastika Putri 2021; Kyriakidou et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that muscle pain peaks 24 hours after exercise (Chang et al, 2021;Hung et al, 2021;Muljadi et al, 2021;Novadri Ayubi et al, 2022). The resulting muscle pain is associated with decreased ROM (Fernández-Lázaro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%